Pengaruh Metode Show And Tell Terhadap Kemampuan Komunikasi Lisan Anak Usia Dini Kelompok B di PAUD Al-Ikhwan Palembang - Leni Marlina; Yecha Febrieanitha Putri; Afra Nabilah Putri (CV. Ulil Albab Corp, 2022)
This research is entitled The Effect of Show and Tell Method on Oral Communication Ability of Early Childhood Group B at PAUD Al-Ikhwan Palembang. This research is motivated because early childhood oral communication skills are very important to be improved and developed since early childhood, and also from the observations of researchers still finding children whose oral communication skills are not in accordance with their level of development. This study aims to determine the feasibility, validity, and practicality of the show and tell method and to determine the effect of the show and tell method on the oral communication skills of early childhood group B in PAUD Al-Ikhwan Palembang. This research is a quantitative research. This study used two classes, namely the experimental group and the control group. This type of research is quasi-experimental, with a nonequivalent control group design research approach. The sample in this study amounted to 30 children in grades B1 and B2 at PAUD Al-Ikhwan Palembang. Data collection techniques using observation, tests, and documentation. The data analysis technique in this study used normality test, homogeneity test, and hypothesis testing t-test. This study resulted that there was a very significant difference between the experimental class which was greater than the control class, based on the calculation of the hypothesis test (t-test) where the t-table value for the 5% significance level was (2.145). It can be concluded that the experimental class t-count value > t-table (2.262 > 2.145) while the control class t-count value > t-table (2.358> 2.145). So the conclusion is Ho is rejected and Ha is accepted. This means that there is an effect of the show and tell method on the oral communication skills of early childhood group B at PAUD Al-Ikhwan Palembang.